The case of Deutsche Telekom: How stock market crashes can persistantly affect household investment decisions - Chi Hyun Kim; Alexander Kriwoluzky (DIW Weekly Report, 2021)
Since decades, only one fourth of German households invest in shares. One exception was during the three IPOs from 1996 to 2000 of the Deutsche Telekom, which gave Germans a taste to enter the stock market. However, the fall in the share price shortly after the second IPO, followed by corruption scandals of the company, put an end to their enthusiasm. The present study based on SOEP data shows that the events surrounding the Deutsche Telekom IPOs led to persistently lower stock market participation-by around 60 percent, even 20 years on. This effect is greater for households that invested directly in T-shares. As a result, confidence in stock investment was permanently destroyed, which can have significantly negative impact on their long-term asset accumulation. In order to counter this loss of confidence, supervisory authorities should examine companies that issue shares to retail investors more closely, in order that cases like Deutsche Telekom and, more recently, Wirecard, do not continue to undermine confidence in the stock exchange. It is also important to provide retail investors with better access to financial education so they can evaluate stock market investments more rationally, thus safeguarding their portfolios.
Keywords: D14; G01; G11; E21; 330; Stock market crashes; emotional tagging; stock market participation